Insights into the strategies used by related group II introns to adapt successfully for the colonisation of a bacterial genome - Martínez-Rodríguez, Laura (RNA Biol, 2014)
Group II introns are self-splicing RNAs and site-specific mobile retroelements found in bacterial and organellar genomes. The group II intron RmInt1 is present at high copy number in Sinorhizobium meliloti species, and has a multifunctional intron-encoded protein (IEP) with reverse transcriptase/maturase activities, but lacking the DNA-binding and endonuclease domains. We characterized two RmInt1-related group II introns RmInt2 from S. meliloti strain GR4 and Sr.md.I1 from S. medicae strain WSM419 in terms of splicing and mobility activities. We used both wild-type and engineered intron-donor constructs based on ribozyme ΔORF-coding sequence derivatives, and we determined the DNA target requirements for RmInt2, the element most distantly related to RmInt1. The excision and mobility patterns of intron-donor constructs expressing different combinations of IEP and intron RNA provided experimental evidence for the co-operation of IEPs and intron RNAs from related elements in intron splicing and, in some cases, in intron homing. We were also able to identify the DNA target regions recognized by these IEPs lacking the DNA endonuclease domain. Our results provide new insight into the versatility of related group II introns and the possible co-operation between these elements to facilitate the colonization of bacterial genomes.